Gain characteristics of ytterbium-doped SiO2–Al2O3–Y2O3 fibers. (9th April 2019) - Li, C Z; Jia, Z X; Cong, Z H; Liu, Z J; Zhang, X Y; Qin, G S; Qin, W P
Abstract: Ytterbium (Yb 3+ )-doped SiO2 –Al2 O3 –Y2 O3 fibers were fabricated by using a molten core method. An Yb 3+ doped yttrium aluminium garnet crystal was used as the core material. The doping concentration of Yb 3+ in the fabricated SiO2 –Al2 O3 –Y2 O3 fibers was measured to be ~3.26 wt%. The background loss of the above fibers was measured to be ~0.0085 dB cm −1 at 1560 nm by using a cutback method. The gain characteristics of the Yb 3+ doped fiber were measured by using a single mode fiber pigtailed 980 nm laser diode as the pump source, and an unit length gain of ~3.9 dB cm −1 was obtained for a signal power of ~0.1 µ W at 1036 nm. Our result showed that the Yb 3+ doped SiO2 –Al2 O3 –Y2 O3 fiber was a potential gain media for constructing narrow line-width fiber lasers.